Implementasi Sistem Informasi Pembayaran Sekolah Berbasis Web untuk Meningkatkan Transparansi dan Efisiensi Administrasi di TK Sarroja - titin Pramesti (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2026)
Digital transformation in school financial management has become crucial to ensuring accountability and operational efficiency, particularly in early childhood education institutions that often still rely on manual processes. This study aims to design and implement a web-based school payment information system at TK Sarroja to address issues of data inefficiency, reporting delays, and the lack of information transparency for parents. The research methodology employed the System Development Life Cycle (SDLC) with the Waterfall model, encompassing requirements analysis, system design, coding, and functionality testing. The results indicate that the system's implementation significantly reduced administrative processing time by up to 70% compared to conventional methods. Furthermore, the real-time transaction history feature has enhanced information accessibility for parents, thereby fostering better fiscal transparency. In conclusion, the digitalization of financial administration through a web platform not only optimizes the performance of administrative staff but also strengthens stakeholder trust in the institution's management integrity. This research provides a practical contribution as a model for modernizing micro-scale school governance in the digital era